UMP’s book on tahfiz education and soft skill won award at the National Book Award 2019 - UMP, PNC (2019)
A book titled, ‘Pendidikan Tahfiz dan Kemahiran Insaniah’ (Tahfiz Education and Soft Skills) published by Universiti Malaysia Pahang (UMP) Publisher won the best general book (education category) at the National Book Award 2019 that was held at Putra World Trade Centre (PWTC) on May 10, 2019. The book was written by Centre for Modern Languages & Human Sciences (CMLHS), Senior Lecturer, Dr. Rashidi Abbas.